Characterization of the intrarenal renin‐angiotensin system in cats with naturally occurring chronic kidney disease. (19th January 2022) - Lourenço, Bianca N.; Coleman, Amanda E.; Berghaus, Roy D.; Tarigo, Jaime L.; Schmiedt, Chad W.; Brown, Scott A.
Abstract: Background: The role of the renin‐angiotensin‐aldosterone system in cats with chronic kidney disease (CKD) is incompletely understood. Objective: To characterize components of the intrarenal renin‐angiotensin system (RAS) in cats with CKD. Animals: Eleven cats with naturally occurring CKD (CKD group) and 8 healthy control cats. Methods: Renal tissue samples were evaluated by reverse‐transcription polymerase chain reaction for renin, angiotensinogen, angiotensin‐converting enzyme (ACE), and angiotensin II type 1 receptor transcript levels, and by liquid chromatography‐mass spectrometry for quantification of angiotensin I, II, III, and IV concentrations. Linear mixed models were used to compare gene transcript levels and concentrations of angiotensin peptides between groups. Results: Cats of the CKD group were significantly older ( P < .001) and more likely to be neutered ( P = .007) than healthy control cats. Kidneys from cats with CKD had significantly higher transcript levels of angiotensinogen ( P < .001) and lower transcript levels of ACE ( P < .001) than those from control cats. Renal angiotensin I concentrations were increased in CKD compared with control kidneys ( P = .001). No other significant differences in renal transcript levels or angiotensin peptide concentrations were noted between groups. Conclusion and Clinical Importance: The intrarenal RAS might be activated in cats with CKD. Small sample size and differences in age, neuter status, and dietary sodium intake between groups might have limited the ability to identify a significant difference in concentration of renal angiotensin II.